2018
DOI: 10.1111/ajo.12826
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, trends and severity of primary postpartum haemorrhage in Australia: A population‐based study using Victorian Perinatal Data Collection data for 764 244 births

Abstract: The incidence of primary postpartum haemorrhage, severe primary postpartum haemorrhage and associated maternal morbidities have increased significantly over time in Victoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 26 publications
4
32
1
1
Order By: Relevance
“…These figures are at least 50% lower than the incidence of 30.9-40.7% observed in Wales in 2017 where quantitative measurement was started at delivery and the same method, confirmed by audit, was used throughout the country. In the context of clinical studies performed more recently, a UK group reported the incidence of PPH ≥500 mL to be 33.7% [11] and in Australia 22% [6] which are in line with our findings established in routine care.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These figures are at least 50% lower than the incidence of 30.9-40.7% observed in Wales in 2017 where quantitative measurement was started at delivery and the same method, confirmed by audit, was used throughout the country. In the context of clinical studies performed more recently, a UK group reported the incidence of PPH ≥500 mL to be 33.7% [11] and in Australia 22% [6] which are in line with our findings established in routine care.…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that blood loss measurement alone does not reduce PPH rates [6,14]. A cluster randomised study comparing systematic use of a collector bag with visual estimation found no difference between the two arms [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrates the persistent increasing rate of PPH and MOH in Ireland in keeping with other studies. (9,11,12) As in other studies (13) we found uterine atony to be the most common cause of MOH. Identifying a cause(s) for this trend is difficult.…”
Section: Principal Findingssupporting
confidence: 83%
“…Therefore our results can only be applied to women with a PPH less than 1500 mL blood loss, which is the majority of all women experiencing PPH. Of all women in labor, 1.4–3.9% progress to more than 1500 mL blood loss [ 3 , 42 ]. Another safety measure was the choice to commence resuscitation at 500 mL of blood loss.…”
Section: Resultsmentioning
confidence: 99%